Three dimensional mechanical model for simulating the NSM FRP strips shear strength contribution to RC beams - Bianco, V. (2009)
Shear strengthening of Reinforced Concrete (RC) beams by means of Near Surface Mounted (NSM) Fiber Reinforced Polymer (FRP) strips is an emerging technique for structural rehabilitation that is gaining increasing interest in the FRP community mainly because of some advantages it provides with respect to the better consolidated technique of the Externally Bonded Reinforcement (EBR). Those advantages encompass, mainly, a better exploitation of material and a higher protection against vandalism along with a relative faster applicability. Yet, the behavior of such NSM FRP strips is extremely complex, as can be gathered by experimental evidence, due to the complex geometry, the non linear mechanical properties of bond, and the scatter affecting the concrete tensile properties along with their non-linearity. In an attempt to provide valuable contribution to a better understanding of their behavior, a three dimensional mechanical model for simulating the shear strength contribution provided by a system of NSM FRPs to a RC beam throughout the loading process was recently developed. Its upgraded version is herein presented along with the main findings. It correctly interprets the experimental evidence taking into account complex phenomena such as the interaction between bond transferred force and concrete fracture along with the interaction between adjacent strips.